THE USE OF LIE LOGIC IN THE PROCESS OF TEACHING CHILDREN - Marianna N. Maksimenko; Rouzan E. Mirzakhanyan; Vladimir A. Mushrub (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
Neo-classical logic was developed in mathematics in the late 19th – early 20th century. One example of neo-classic logic is lie logic. The article on the basis of analyzing the stages of psychical development of children carried out by J. Piaget, a prominent Swiss psychologist and philosopher builds lie logic and discusses different aspects of its use in pedagogic theory and practice. On the basis of their personal pedagogical experience the authors substantiate the idea that people at the same stage of development demonstrate similar forms of cognitive abilities. They also conduct comparative analysis of classical truth logic and lie logic from the point of view of mathematic logic.